Effects of whole-body vibration plus hip-knee muscle strengthening training on adult patellofemoral pain syndrome: a randomized controlled trial. Issue 20 (25th September 2022) - Wu, Zhangxiang; Zou, Zhi; Zhong, Jiugen; Fu, Xinbo; Yu, Ligen; Wang, Jinzhu; Wang, Xin; Wu, Qianwen; Hou, Xiaohui
Abstract: Purpose: To investigate whether whole-body vibration (WBV) plus hip-knee muscle strengthening is more efficient in relieving pain and improving function than hip-knee strengthening alone. Methods: Thirty-six participants with patellofemoral pain syndrome (PFPS) were recruited and randomly allocated to either the (1) hip-knee strengthening only (HK group, n  = 18) or (2) WBV plus hip-knee strengthening group (WHK group, n  = 18). All participants attended 18 physiotherapy sessions (3 sessions/week, 40 min/session) over 6 weeks. Data on symptoms, function, surface electromyography (sEMG) signals from the vastus medialis and gluteus medius, and quality of life were evaluated at baseline (T0 ), 6 weeks after (T6 ), and the 12-week follow-up (T18 ). Results: Significant group × time interactions were found for the VAS score ( p  < 0.001) and vastus medialis performance ( p  ≤ 0.015). The WHK group exhibited a greater pain relief than did the HK group at T18 ( p  ≤ 0.014). The WHK group exhibited significantly larger improvements in the RMS value than did the HK group at T6 ( p  ≤ 0.011). Conclusions: The present study shows that 6 weeks of WBV plus hip-knee strengthening can improve vastus medialis performance and maintain long-term pain relief to a significantly greater extent than can hip-knee strengthening alone. IMPLICATIONS FOR REHABILITATION: The present study shows that 6 weeks of WBV plus hip-knee strengthening can improve vastus medialis performance and maintain long-term pain relief to a significantly greater extent than can hip-knee strengthening alone.